Salivary Metabolites Profiling in Primary Sjögren Syndrome: Identifying Purine as a Potential Biomarker - Abd Aziz, Fatin Izzatti Amalina; Raja, Jasmin; Al-Maleki, Anis Rageh; Ramanathan, Anand (Malaysian Journal of Medical Sciences, 2026)
Background: Salivary biomarkers such as proteins, metabolites, hormones, and nucleic acids can provide biological information for a variety of medical problems, such as cancer, stress, systemic disorders, and neurodegenerative and infectious diseases. The proteome and metabolomic alterations observed in saliva appear to match those observed in blood, reflecting the cells’ cellular activity and physiological status. Methods: This is a case-control study that included 10 individuals [5 primary Sjögren syndrome (pSS) and 5 healthy controls (HCs)], each contributing two salivary matrices (unstimulated saliva and oral rinse), resulting in a total of 20 samples for metabolomic analysis (n = 20 samples from n = 10 participants). Salivary metabolite profiling was performed using liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS), with the HMDB, BRMB, and METLIN databases used for metabolite identification. Chemometric analysis (Unscrambler software) and statistical analysis (SPSS) were used to assess the diagnostic potential of the identified metabolites. Results: LC-Q-TOF-MS identified 269 metabolites, with purine significantly upregulated in pSS patients compared to HCs (P = 0.01). Upregulation of purine metabolism may indicate an inflammatory response in pSS patients. Conclusion: In this study, we found that there was a significant difference in the salivary metabolites profile (purine) between patients with pSS and HCs; thus, analysing purine metabolites in saliva may serve as a potential non-invasive candidate biomarker that warrants validation in larger cohorts for discriminating between patients with pSS from HCs and monitoring disease progression.